Effect of Ultrasonic Power on Microstructure and Mecha- nical Properties of Mg-3RE-3Zn-0.7Y Alloy. Issue 1 (January 2016) - Xiaogang, Fang; Shusen, Wu; Li, Zhao; Shulin, Lü; Ping, An
Abstract: The Rare Earth (RE) contained Mg cast alloys have large potential in heat-resistant applications, if the RE-rich intermetallic compounds can be refined during the casting process. In the present research, the effect of ultrasonic vibration (USV) with different powers on the microstructure and the mechanical properties of the semi-solid Mg-3RE-3Zn-0.7Y alloys has been investigated. The Mg alloy melt at temperature of 20~40 °C above the liquidus was exposed to USV for 90 s at different powers from 800 W to 1200 W, and the exposure was ended at about 10 °C below the liquidus. The results show that a good semi-solid slurry with fine and spherical α -Mg particles can be obtained, and the primary α -Mg crystals have an average particle size of 55 μm and average shape coefficient of 0.63 after USV with 1000 W power. After USV treatment with the power of 1000 W, the ultimate tensile strength and the elongation of the cast samples increase by 25.2% and 93.5%, respectively, compared with those of the samples without USV treatment. It can be concluded that ultrasonic vibration is a good method to prepare semi-solid slurry of Mg alloy with fine and relatively round primary crystals due to cavitation and acoustic streaming effects.